2011
DOI: 10.1254/jphs.11r02cp
|View full text |Cite
|
Sign up to set email alerts
|

Adult Neurogenesis Is Regulated by Endogenous Factors Produced During Neurodegeneration

Abstract: Abstract. Adult neurogenesis is the process of generating new neurons that become integrated into existing circuits after fetal and early postnatal development has ceased. In most mammalian species, adult neurogenesis only appears to occur in the olfactory bulb and the hippocampus, where neural stem/progenitor cells (NPCs) exist to create new neurons. In adult neurogenesis, microenviromental change is thought to provide a specific modulation for maintaining the multi-potent state of these NPCs. Neurodegenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 31 publications
(30 reference statements)
2
31
0
Order By: Relevance
“…Thus, it has been proposed that neurotransmitters may act directly as paracrine or autocrine factors to NPCs under physiological conditions. Indeed, systemic administration of NMDA decreases proliferation of NPCs in the adult murine hippocampal dentate gyrus [29], whereas administration of a dopamine D3 agonist increased proliferation of NPCs in the adult murine subventricular zone [28]. In the present study, we demonstrated the possibility that glycine enhances proliferation of NPCs.…”
Section: Discussionsupporting
confidence: 52%
“…Thus, it has been proposed that neurotransmitters may act directly as paracrine or autocrine factors to NPCs under physiological conditions. Indeed, systemic administration of NMDA decreases proliferation of NPCs in the adult murine hippocampal dentate gyrus [29], whereas administration of a dopamine D3 agonist increased proliferation of NPCs in the adult murine subventricular zone [28]. In the present study, we demonstrated the possibility that glycine enhances proliferation of NPCs.…”
Section: Discussionsupporting
confidence: 52%
“…The subventricular zone, subgranular layer of the dentate gyrus (DG), and cortex are the main sites of adult neurogenesis (Gould et al, 1999;Luskin & Boone, 1994;Palmer et al, 2000;Seki et al, 2007;Yoneyama et al, 2011). Newly-born neurons during adult neurogenesis have the ability to integrate into previously established neuronal networks (Kee et al, 2007;Markakis & Gage, 1999;Sandoval et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Newly-born neurons during adult neurogenesis have the ability to integrate into previously established neuronal networks (Kee et al, 2007;Markakis & Gage, 1999;Sandoval et al, 2011). Alteration of neurogenesis under different experimental and pathological conditions has been described to a great extent (Rodriguez & Verkhratsky, 2011;Sandoval et al, 2011;Winner et al, 2011;Yoneyama et al, 2011;Yu et al, 2009). Significant decreases of neurogenesis have been found in neurodevelopmental (Contestabile et al, 2007;Guidi et al, 2008Guidi et al, , 2010 and in neurodegenerative diseases (Rodriguez & Verkhratsky, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, cytokines/chemokines and other pro-and anti-inflammatory molecules have been shown to regulate NSC/NPC survival, proliferation, fate, and migration (reviewed in Ref. 19). However, the effect of infiltrating innate immune cells and humoral components of the innate immune response, for example, neutrophils, macrophages (Mf), and cytokines/ proteins of the complement cascade, on stem cells remains to be elucidated.…”
mentioning
confidence: 99%